52x-3 – 2.52 = 52.3;
52×x-3-2×52 = 52×3
Bài 1: tìm x
c) \(|\) x \(|\) = 3,5
d) \(|\) x \(|\) = -2,7
e) \(|\) 1 - x \(|\) + 0,73 = 3
f) 52 . 73 . 11x + 52 . 72 .11 = 0
g) (3 . 5 + 5 . 7)x + ( 3 . 5 + 5 . 7) + (3 . 5 + 5 . 7) = 0
h) 52 . 72 . 112x - 52 . 72 . 114 = 0
l) \(|\) x + \(\dfrac{3}{4}\) \(|\) - 5 = -2
c) \(\left|x\right|=3,5\Rightarrow\left[{}\begin{matrix}x=3,5\\x=-3,5\end{matrix}\right.\)
d) \(\left|x\right|=-2,7\Rightarrow x\in\varnothing\)
l) \(\left|x+\dfrac{3}{4}\right|-5=-2\Rightarrow\left|x+\dfrac{3}{4}\right|=3\)
\(\Rightarrow\left[{}\begin{matrix}x+\dfrac{3}{4}=3\\x+\dfrac{3}{4}=-3\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=3-\dfrac{3}{4}\\x=-3-\dfrac{3}{4}\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=\dfrac{9}{4}\\x=\dfrac{15}{4}\end{matrix}\right.\)
Đính chính câu l \(x=-\dfrac{15}{4}\) không phải \(x=\dfrac{15}{4}\)
c) x = 3,5 hoặc -3,5
d) x = -2,7
e) x = -1,27
f) x = 0
g) x = -2
h) x = 0
l) x = 9/4
x = -15/4
tim x 52x-3-2×52 = 52×3
52 x X - 3 x 52 = 53 x 3
<=> 52 * x - 156 = 159
<=> 52 * x = 159 + 156
<=> 52 * x = 315
=> x = 315 : 52
=> x = .....................Tự tính
52(x-3)=53*3
x-3=53*3/52= 3.0.....
Bạn ghi đề sai ak? Nếu tính ra thì số lớn lắm
52 x X - 156 = 159
52 x X = 159 + 156
52 x X =315
X = 315 : 52 = ........
Tính bằng cách thuận tiện nhất :
19 x ( 52 + 38 ) - 9 x ( 52 + 38 )
2/5 : 3/7 x 3/7 : 2/5 + 2019
a) \(19\times\left(52+38\right)-9\times\left(52+38\right)=\)
\(=\) \(19\times90-9\times90\)
\(=90\times\left(19-9\right)\)
\(=90\times10\)
\(=900\)
b) \(\dfrac{2}{5}\div\dfrac{3}{7}\times\dfrac{3}{7}\div\dfrac{2}{5}+2019=\)
\(=\left(\dfrac{2}{5}\div\dfrac{2}{5}\right)\times\left(\dfrac{3}{7}\div\dfrac{3}{7}\right)+2019\)
\(=1\times1+2019\)
\(=2019\)
tim x 52x_3-2×52 = 52×3
Tìm x biết:
1. 52x - 3 - 2 . 52 = 52 . 3
2. 41 - 2x+1 = 9
3. 65 - 4x+2 = 20140
1: =>\(5^{2x-3}=5^2\cdot3+5^2\cdot2=5^2\cdot5=5^3\)
=>2x-3=3
=>2x=6
=>x=3
2: \(41-2^{x+1}=9\)
=>\(2^{x+1}=32\)
=>x+1=5
=>x=4
3: =>\(4^{x+2}=65-1=64\)
=>x+2=3
=>x=1
\(5^{2x-3}-2.5^2=5^2.3\\ 5^{2x-3}=5^2.3+5^2.2\\ 5^{2x-3}=5^2.\left(3+2\right)\\ 5^{2x-3}=5^2.5\\ 5^{2x-3}=5^3\\ \Rightarrow2x-3=3\\ 2x=3+3\\ 2x=6\\ x=\dfrac{6}{2}\\ Vậy:x=3\)
\(41-2^{x+1}=9\\ 2^{x+1}=41-9\\ 2^{x+1}=32=2^5\\ \Rightarrow x+1=5\\ \Leftrightarrow x=5-1=4\\ ---\\ 65-4^{x+2}=2014^0\\ 65-4^{x+2}=1\\ 4^{x+2}=65-1\\ 4^{x+2}=64=4^3\\ \Rightarrow x+2=3\\ Vậy:x=1\)
52x – 3 – 2 . 52 = 52. 3
5²ˣ⁻³ - 2.5² = 5².3
5²ˣ⁻³ - 2.25 = 25.3
5²ˣ⁻³ - 50 = 75
5²ˣ⁻³ = 75 + 50
5²ˣ⁻³ = 125
5²ˣ⁻³ = 5³
2x - 3 = 3
2x = 3 + 3
2x = 6
x = 6 : 2
x = 3
Tìm x
52x-3 - 2 . 52 = 52 . 3
\(5^{2x-3}-2.5^2=5^2.3\)
\(\Rightarrow5^{2x-3}=5^2.3+2.5^2\)
\(\Rightarrow5^{2x-3}=5^2\left(3+2\right)\)
\(\Rightarrow5^{2x-3}=5^2.5\)
\(\Rightarrow5^{2x-3}=5^3\)
\(\Rightarrow2x-3=3\)
\(\Rightarrow2x=6\)
\(\Rightarrow x=3\)
Vậy x = 3
#kễnh
52x-3 - 2×52 = 52×3
52x-3 - 2 x 52 = 52 x3
52x-3 - 2x52 = 156
52x-3 - 104 = 156
52x-3 =156 + 104
52x-3 = 260
x-3 = 260:52
x-3 = 5
x=5+3
x=8
Vậy x=8